2018
DOI: 10.1177/0256090917750263
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural Commodity Trading: Is it Destabilizing Spot Markets?

Abstract: Executive Summary The future trading has been held responsible by certain political and interest groups of enhancing speculative trading activities and causing volatility in the spot market, thereby further spiralling up inflation. This study examines the effect of future of trading activity on spot market volatility. The study first determined the Granger causal relationship between unexpected future trading volume and spot market volatility. It then examined the Granger causal relationship between unexpecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…Nath and Lingareddy (2008) emphasized that trading in commodity futures contributed to an increase in inflation, as results showed that during the time period of future trading, the spot price of selected commodities and their volatilities had reported a remarkable increase. This is in line with the recent findings of Gupta et al (2018) stating that future market leads to volatility in the spot market. Some studies have stated that future prices are independent and past prices have no role in the contribution of future price prediction.…”
Section: Review Of Literaturesupporting
confidence: 92%
“…Nath and Lingareddy (2008) emphasized that trading in commodity futures contributed to an increase in inflation, as results showed that during the time period of future trading, the spot price of selected commodities and their volatilities had reported a remarkable increase. This is in line with the recent findings of Gupta et al (2018) stating that future market leads to volatility in the spot market. Some studies have stated that future prices are independent and past prices have no role in the contribution of future price prediction.…”
Section: Review Of Literaturesupporting
confidence: 92%
“…Other import studies describing various liquidity metrics and dimensions are Sarr and Lybek (2002); Fleming (2003); Goyenko et al (2009); International Monetary Fund (2015); Diaz and Escribano (2017); Broto and Lamas (2020); O'Sullivan and Papavassiliou (2019); Clancy et al (2019); Barth and Kahn (2020); Jiang et al (2020); Gupta et al (2018); Kandil (2018) and White et al (2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Yang et al (2005) identified that an unexpected increase in futures trading volume leads to spot price volatility for agricultural commodities. Nath and Lingareddy (2008) and Gupta et al (2018) studied the volatility of Indian agrarian commodities and recognized that speculation and volatility in the futures market have destabilization impact on the spot market. Manogna and Mishra (2020), Maitra (2018) highlighted significant volatility spillover for GS futures markets.…”
Section: Destabilizing Impact Of Speculative Tradingmentioning
confidence: 99%